A mediação do professor no processo de seleção e condução de textos literários : uma prática da leitura literária para alunos de Ensino Fundamental - Lessa, Heloísa Maria Marques (2015)
The objective of this research was to evaluate the importance of the teacher in the selection and conduct of literary texts in the formation of literary readers in Elementary Education. We treat the Literary Literacy which is a special kind of literacy that has inherent own nuances of literary reading. We understand that it is a social practice of school responsibility and that is not a ready and finished skill to read literary texts. We begin with the knowledge of the results of the third edition of the survey Reading Pictures in Brazil, promoted by the IPL, which had the support of Abrelivros, CBL and SNEL from June 11 to July 3, 2011. It showed that the respondents do not have reading habits because they are not motivated in the family environment, as well as revelead that the teacher plays a vital and necessary role in mediation between the student and the book. Our research has as corpus students in a fifth grade classroom of Elementary School I of the Escola Estadual Dom Eduardo and students in a sixth grade of Elementary School II of the Escola Estadual Professora Corina de Oliveira. Both schools are located in the urban area of the city of Uberaba - MG. The first analysis concerns the reader s habits of fifth graders, carried out through questionnaires. The second analysis concerns the considerations that students did after the selection, adoption and conduct of two works of Juvenile Literature - in which we use a methodological procedure called \"Basic Sequence\", suggested by Rildo Cosson in his book Letramento Literário: teoria e prática (Literary Literacy: theory and practice) (2009). After the adoption procedures, conduct and evaluation of the readings of works Angélica by the author Lygia Bojunga Nunes and O olho de vidro do meu avô, by the author Bartolomeu Campos de Queirós, proceed to the application of questionnaires to collect data to support analysis the performance of the teacher\'s mediation in the selection and in the conduct of readings of the works in question.